Application of bagasse and coir as sorbent dust for heavy metal and dye remediation from aqueous solution / Norain Isa, Nor Aimi Abdul Wahab and Dr. Nor Aziyah Bakhari - Isa, Norain; Abdul Wahab, Nor Aimi; Bakhari, Nor Aziyah (Research Management Institute (RMI), 2012)
Dyes, pigments and heavy metals represent common and dangerous pollutants, originating in large quantities from dye manufacturing, textile as well as pulp and paper industries. They are emitted into wastewaters and produce difficult to treat water contamination, as the colour tends to persist even after the conventional removal processes [1,2]. The conventional techniques used for dyes and heavy metal removals are expensive, have average efficiency and are running in sequential steps. For example, on the commercial scale the ion-exchangers and activated carbons are used, however, with certain disadvantages. The activated carbon is a great adsorbent for dyes but de-sorption and regeneration is difficult under common conditions and the overall process becomes expensive. Moreover, its efficiency in heavy metals removal is average [3,4,5]. Removal of heavy metals and dyes using agricultural waste has been massively investigated due to the abundance of agricultural-related material and its low cost [6,7,8,9]. Various investigated agricultural waste include rice husk ash [10], sunflower stalks [11], sago waste [12] and papaya wood [13]. In this study, bagasse and coir has been choosen as the adsorbent for heavy metal (Cd(ll)) and dyes (methylene and congo red) removal.